Problematika Alih Media Alat Peraga Berbasis Surface kepada Alat Peraga Berbasis Screen - Sulaiman, Naniwati; Palit, Rene Arthur (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2024)
The global health crisis due to the COVID-19 pandemic has impacted all areas of human life. Humans must rearrange their way of life, including the way of worship. Sunday school services that were previously luring at the church, have now turned into daring worship at home. In the practice of telling stories daring, it turns out that Surface-based media, such as print media, which were originally effective in face-to-face situations, are now less powerful in front of the camera. All visual aids used to tell stories to Sunday school children cannot simply be used in front of a screen in daring worship. The reason is that screen-based media has different characteristics from Surface-based media. So, illustrations and types of luring props cannot simply be used in an daring situation. Visual aids in face-to-face situations cannot be equated with daring situations. This study aims to apply Surface-based visual aids to screen-based media. To achieve this goal, literature and experimental study methods are used. First, a literature study will be conducted on the characteristics of visual aids. Next, a sample of Surface-based Sunday school story props will be selected which is designed to be a screen-based teaching aid. Then the results of the transformation of the props will be tested on Sunday school children. The final step is the completion of the work. It is hoped that the findings of this study can provide input for the design of daring Sunday school visual aids. In general, it can be useful for the development of visual communication design media.